Bacteria From the Southern Gulf of Mexico: Baseline, Diversity, Hydrocarbon-Degrading Potential and Future Applications - Rodríguez-Salazar, Julieta; Loza, Antonio; Ornelas-Ocampo, Katya; Gutierrez-Rios, Rosa Maria; Pardo-López, Liliana (Frontiers in Marine Science, 2021)
The Gulf of Mexico Research Consortium (CIGoM) was founded in 2015 as a consortium of scientific research and consulting services, specializing in multidisciplinary projects related to the potential environmental impacts of natural and human-induced oil spills in marine ecosystems, to understand and act in case of possible large-scale oil spills in the Gulf of Mexico. The consortium is composed of more than 300 specialized researchers trained at the most recognized Mexican institutions. Among the main lines of interest are, to develop the first baseline of the bacterial community inhabiting the Gulf of Mexico, to investigate the natural degradation of hydrocarbons by bacterial communities and microbial consortia and the identification and characterization of industrially relevant enzymes. In this manuscript, we present a review of the taxonomy found in samples of water and sediments taken from the Perdido Fold Belt (northwest), Campeche Knolls (southeast) and sediments of the southwest region of the Gulf of Mexico. We report here some efforts of bioprospecting of strains and enzymes with hydrocarbon degradation capacity, using by sequence and function screening methodologies; we also report the construction and exploration of metagenomic libraries using metagenomic DNA from consortia or environmental samples collected off the coast of Tamaulipas in the Perdido Escarpment area, at the northwest of the Gulf of Mexico, and from sediment samples from the southwest of the Gulf of Mexico on the coast of Campeche, looking for enzymes with high biotechnological potential as lipases and dioxygenases with novel characteristics and specific hydrocarbon-degrading strains that could be used in bioremediation processes by immobilization techniques or to be used as biosensors and mesocosms assays.